1991
DOI: 10.1128/aac.35.7.1376
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cefotaxime and desacetylcefotaxime in patients with liver disease

Abstract: The dispositions of cefotaxime and its metabolite desacetylcefotaxime were investigated in patients with different forms of chronic parenchymal liver disease (CPLD). A total of 31 subjects (27 patients and 4 controls) received a single 2-g dose of cefotaxime by infusion, and serial blood samples were drawn. The area under the concentration-time curve ranged from 176 to 241 micrograms.h/ml, the apparent half-life ranged from 1.49 to 2.42 h, and clearance ranged from 2.06 to 3.10 ml/min/kg in patients with four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The resulting cefotaxime typical CL value (11.1 L/h for a subject with ICU weight of 92 kg and with eCLcr of 94 mL/min) is in line with previously reported 10–13 L/h in patients with liver disease [ 23 ] and higher than 5.4 L/h in elderly patients [ 8 ]. Clearance of 15–17 L/h in healthy adult populations [ 21 , 22 ] is higher than in this ICU population as expected due to acute kidney injury in severe illness despite occasional cases of ARC.…”
Section: Discussionsupporting
confidence: 91%
“…The resulting cefotaxime typical CL value (11.1 L/h for a subject with ICU weight of 92 kg and with eCLcr of 94 mL/min) is in line with previously reported 10–13 L/h in patients with liver disease [ 23 ] and higher than 5.4 L/h in elderly patients [ 8 ]. Clearance of 15–17 L/h in healthy adult populations [ 21 , 22 ] is higher than in this ICU population as expected due to acute kidney injury in severe illness despite occasional cases of ARC.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic liver disease affects drug disposition more than any other form of liver disease. For some drugs, such as cephalosporins, it has been reported that alterations in PK parameters in chronic parenchymal liver disease were highly correlated to clinical indices of hepatic impairment and the stages of liver impairment (Ko et al, 1991). More typically, however, the effects of liver diseases are unpredictable, lack sensitivity and do not correlate well with the type of liver damage, its severity, or liver laboratory test results (Davis, 2007).…”
Section: Hepatic Impairmentmentioning
confidence: 99%
“…CTX and d-CTX were found to interact synergistically against many microorganisms [17,19], allowing for possible dose reductions and for some CTX-resistant or moderately resistant organisms to be treated safely by high-dose CTX regimens [20]. CTX is mainly eliminated by the liver, and several authors have shown a prolonged serum half-life of CTX in cirrhotic patients [11,13,14]. The same phenomenon occurs in patients with reduced renal function in whom serum levels of CTX and d-CTX are much higher than in normal subjects, and the ratio of d-CTX to CTX increases significantly [9].…”
mentioning
confidence: 98%